2014
DOI: 10.2196/jmir.3348
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effects in Regular Practice of E-Communication and Web-Based Self-Management Support Among Breast Cancer Patients: Preliminary Results From a Randomized Controlled Trial

Abstract: BackgroundWhile Web-based interventions have been shown to assist a wide range of patients successfully in managing their illness, few studies have examined the relative contribution of different Web-based components to improve outcomes. Further efficacy trials are needed to test the effects of Web support when offered as a part of routine care.ObjectiveOur aim was to compare in regular care the effects of (1) an Internet-based patient provider communication service (IPPC), (2) WebChoice, a Web-based illness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
254
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(270 citation statements)
references
References 56 publications
3
254
0
13
Order By: Relevance
“…Evaluative research in this area has found a mixed picture in terms of the impact of patient monitoring on self-management and patient outcomes. 313,318,[372][373][374][375] Mixed-methods research is needed to explore the contexts in which and mechanisms through which these interventions achieve their intended outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Evaluative research in this area has found a mixed picture in terms of the impact of patient monitoring on self-management and patient outcomes. 313,318,[372][373][374][375] Mixed-methods research is needed to explore the contexts in which and mechanisms through which these interventions achieve their intended outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Borosund et al (29) and Ruland et al (30) demonstrated that an internet-based messaging system to provide breast cancer patients with the ability to send questions to care providers and receive responses, a discussion forum for communicating with other patients, and a blogging tool resulted in significant, but quite small, improvements with respect to anxiety, depression, and symptom distress relative to a usual care control group. Use of the social tools, such as the discussion forum and blogs was limited, such that the median number of posts per participant was zero in both the discussion forum and the blogs and an average of 1 advice message was sent, although participants did spend time reading what others had posted.…”
Section: Introductionmentioning
confidence: 99%
“…Third, professional characteristics influence the use of the tools. For instance, healthcare providers beliefs (is the tool useful for professionals and patient);2224 the fact that general practitioner adoption of e-mail remains low even though it is easily available26 and professionals do not give equal priority to e-communication (nurses are more conscientious than physicians);22 low computer literacy, insufficient basic formal training in health IT applications, physicians’ concerns about more work; workflow issues; problems related to new system implementation, including concerns about confidentiality of patient information; depersonalization; incompatibility with current health care practices; lack of standardization and problems with reimbursement 20. Fourth, barriers to implementation can also be found at the institutional level.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, barriers to implementation can also be found at the institutional level. There are concerns about confidentiality and security25 unclarity in the implementation process concerning decisions about roles, sufficient time and sufficient competence of professionals 22 , 24…”
Section: Introductionmentioning
confidence: 99%